EFEKTIVITAS PELAKSANAAN PEMOTONGAN PPH PASAL 21 OLEH WAJIB PAJAK BADAN TERHADAP HONORARIUM YANG DIBERIKAN KEPADA NOTARIS/PPAT DI KOTA LHOKSEUMAWE - AQRA RIZPADILLAH CHEMA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Dr. Bastari, MM3. Dr. Utary Maharany Barus, SH, MHum According to Article 21, paragraph 1, letter d of Law on Income Tax (UU PPh), PPh (income tax) withholding, concerning occupation, service, and activity on behalf of and in any types received by a Taxpayer in Indonesia, has to be paid by a Corporate which pays fee to a Notary as a professional who receives earnings with PPh withholding Article 21. The result of the research showed that according Article 21 of Law on PPh, a Corporate has the attribution authority directly in certain articles of legal provisions to do PPh witholding Article 21 on the fee of Notary/PPAT. However, PPh withholding Article 21 at Lhokseumawe is not effective. Therefore, to get legal protection the Notary/PPAT has the right to file complaint according to Article 25 of UU KUP. The research used juridical empirical and descriptive analytic method. Primary data were gathered by using questionnaires and analyzed by using qualitative method.Keywords: Income Tax, PPh Article 21, Fee, Notary